2000
DOI: 10.1074/jbc.275.13.9690
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Na+-independent Neutral Amino Acid Transporter That Associates with the 4F2 Heavy Chain and Exhibits Substrate Selectivity for Small Neutral d- and l-Amino Acids

Abstract: A cDNA was isolated from the mouse brain that encodes a novel Na ؉ -independent neutral amino acid transporter. The encoded protein, designated as Asc-1 (asc-type amino acid transporter 1), was found to be structurally related to recently identified mammalian amino acid transporters for the transport systems L, Asc-1 mRNA was detected in the brain, lung, small intestine, and placenta. The functional properties of Asc-1 seem to be consistent with those of a transporter subserving the Na ؉ -independent small neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
237
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(251 citation statements)
references
References 44 publications
13
237
0
1
Order By: Relevance
“…Moreover, among the heteromeric amino acid transporters that mediate exchange of neutral amino acids, only LAT-2 transport activity, but not LAT-1, asc-1 and asc-2, is expressed in the basolateral domain of OK cells. This is in full agreement with the expression of these transporters in the epithelial cells of the renal proximal tubule; LAT-1 is barely expressed in human and mouse kidney (38,39), asc-1 is not expressed in kidney (28), asc-2 is localized in collecting ducts in mouse kidney (29), and only LAT-2 is conspicuously expressed in the epithelial cells of the renal proximal tubule and the small intestine (21)(22)(23)40).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Moreover, among the heteromeric amino acid transporters that mediate exchange of neutral amino acids, only LAT-2 transport activity, but not LAT-1, asc-1 and asc-2, is expressed in the basolateral domain of OK cells. This is in full agreement with the expression of these transporters in the epithelial cells of the renal proximal tubule; LAT-1 is barely expressed in human and mouse kidney (38,39), asc-1 is not expressed in kidney (28), asc-2 is localized in collecting ducts in mouse kidney (29), and only LAT-2 is conspicuously expressed in the epithelial cells of the renal proximal tubule and the small intestine (21)(22)(23)40).…”
Section: Discussionsupporting
confidence: 68%
“…The following criteria were used to detect LAT-2 activity: (1) L-alanine is transported via LAT-2, asc-1, and asc-2 (22,23,28,29), but it is not transported via LAT-1 (30,31); (2) transport of L-alanine via LAT-2, but not via asc-1 and asc-2, is inhibited by BCH and L-tyrosine (23) To check the amino acid exchanger activity of the LAT-2-related L-system (21,22,24), polarized cells were loaded on the basolateral and apical membranes with the radioactive substrate (L-[ 3 H] leucine or L-[ 3 H] alanine), and the efflux across the basolateral membrane was measured. The efflux of Lleucine or L-alanine trans-stimulated by LAT-2 substrates was mostly sodium independent.…”
Section: Ok Cells Express Lat-2 and Y ϩ Lat-1 Related Transport Activmentioning
confidence: 99%
“…Consistently, our data indicated that proliferation of MDA-MB-231(SA) cells in serine-free conditions was strongly inhibited by PSAT1 knockdown. Serine is transported in and out of cells via amino acid transporters: the Na+-dependent transporters ASCT1 (SLC1A4) and ASCT2 (SLC1A5) [21,22], the system A transporters SA1 (SLC38A1) and SA2 (SLC38A2) [23] and the Na+-independent alanineserine-cysteine transporter 1 (Asc-1 (SLC7A10)) [24]. One of these transporters, In addition to cell proliferation, our data suggest that enhanced serine biosynthesis may promote other aspects in the metastatic cascade.…”
Section: Discussionmentioning
confidence: 99%
“…It is a Na + -independent amino acid transporter with homology to the system L transporter (LAT) family. (8,9) Although Asc-1 exhibits high affinity for small, neutral L-amino acids such as alanine, it also has high affinity for D-amino acids, including D-serine, (8)(9)(10) a co-agonist of NMDAR. (11) Asc-1 is widely distributed throughout the brain, largely localized to presynaptic nerve terminals (10) but in significant overlap with brain regions expressing and releasing D-serine from glial cells.…”
Section: Introductionmentioning
confidence: 99%